2010
DOI: 10.1007/s10336-009-0488-x
|View full text |Cite
|
Sign up to set email alerts
|

Arrival date and territorial behavior are associated with corticosterone metabolite levels in a migratory bird

Abstract: Glucocorticoids promote the mobilization of energy stores and they may facilitate the expression of energetically expensive functions. Early arrival on the breeding grounds in migratory species and territorial competition are energetically demanding activities that may be supported by elevated baseline glucocorticoid levels. Here, we evaluated the associations between the baseline levels of excreted corticosterone (CORT) metabolites of male Pied Flycatchers (Ficedula hypoleuca) just after arriving on their bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 87 publications
(108 reference statements)
2
18
0
Order By: Relevance
“…WITH THE RELATIVE ease and aífordability of modern labora-behavioral studies (Dolan et al 2007, Baienger et al 2009); to meatory techniques, increasing numbers of field biologists regularly col-sure metabolites (Lyons et al 2008, Lobato et al 2010, hormones lect blood samples from their study organisms to extract DNA for (Spinney et al 2006, Van Hout et al 2010, or stable isotopes The Auk, Vol. 128, Number 3, pages 514-521.…”
Section: Análisis Multiestado De Marcado-recaptura Revela Ausencia Dementioning
confidence: 99%
“…WITH THE RELATIVE ease and aífordability of modern labora-behavioral studies (Dolan et al 2007, Baienger et al 2009); to meatory techniques, increasing numbers of field biologists regularly col-sure metabolites (Lyons et al 2008, Lobato et al 2010, hormones lect blood samples from their study organisms to extract DNA for (Spinney et al 2006, Van Hout et al 2010, or stable isotopes The Auk, Vol. 128, Number 3, pages 514-521.…”
Section: Análisis Multiestado De Marcado-recaptura Revela Ausencia Dementioning
confidence: 99%
“…According to the "Challenge Hypothesis", males are able to increase testosterone levels relative to the territorial challenge to facilitate aggressive behavior during the breeding season (Wingfield et al 1990). For instance, Lobato et al (2010) recently found that early-arriving male Pied flycatchers (Ficedula hypoleuca) displayed stronger territoriality and had higher corticosterone metabolite levels compared to late-arriving males. However, the aggressive behavior of males is not always associated with high testosterone levels, and the reasons for this are still under debate (reviewed by Goymann 2009).…”
Section: Discussionmentioning
confidence: 98%
“…This evidence accords well with the hypothesis of costs which predicts patch decrements after higher levels of breeding exertion (Gustafsson et al ). Early breeding males are probably those suffering higher reproductive costs due to the costs of migrating early (Ruiz‐de‐Castañeda et al ) and the stiffer competition for nest cavities at the beginning of the breeding season (Lobato et al ). According to the cost hypothesis, we should expect these males to show patch decreases compared with late breeders as found for forehead patches.…”
Section: Discussionmentioning
confidence: 99%
“…UV reflectance of white patches has been analyzed in other studies of the species (Lehtonen et al , Sirkiä and Laaksonen ). In this study we focus on the area of these plumage patches as in other studies of the species (Galván and Moreno , Lehtonen et al , Lobato et al , Moreno et al , , , Cantarero et al , , Laaksonen et al , Sirkiä et al , Plaza et al ). Moreover, we have previously shown that area and UV reflectance of wing patches are positively correlated, at least in females (Cantarero et al ).…”
Section: Introductionmentioning
confidence: 99%